Internalisasi Nilai-Nilai Moderasi Beragama dalam Pendidikan Karakter di Sekolah Dasar - Umah, Restu Yulia Hidayatul; Werdiningsih, Wilis; Anggraini, Yulia (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Elementary school age is an age that is vulnerable to deviant behavior. Things that are considered fun will continue to be done even though it is deviant behavior. For example, the frequency of seeing